Investigating the susceptibility of foreskin myeloid cells to ex vivo HIV infection - Nleya, Bokani (Department of Pathology, 2023)
Background: HIV/AIDS remains a global concern that, although manageable using anti-retroviral therapy (ART), is still eluded by a cure with paucity of knowledge regarding its acquisition and spread especially through the male genital tract (MGT)1–4. Several authors have shown the human foreskin to be an effective mucosal effector site with heterogenous populations of innate and adaptive immune cells, that are permissive to HIV infection5–8. In support of this, medical male circumcision (MMC), has been reported to confer up to 60 % risk reduction in HIV acquisition9–17. Most studies have focused on investigating blood lymphoid immune cells and their interaction with HIV-1, this study sought to elucidate the myeloid cell composition of the inner and outer foreskin, and to investigate the susceptibility of these cells to ex vivo HIV infection by (i) Isolating migratory and non-migratory Langerhans cells (LCs) and “macrophage-like” cells from the foreskin epidermis (ii) Immunophenotyping and characterising foreskin LCs and “macrophage-like” cells using CD4+CCR5+ as proxy for HIV susceptibility, HLA-DR+CD80/86+ for maturation, and the mannose receptor, DC-SIGN and Siglec-1 as HIV attachment factors and (iii) Investigating the HIV susceptibility of foreskin epidermal cells using an optimised ex vivo pluricellular foreskin infection model of suspension cells. Methodology: Foreskin specimen were obtained from 60 seronegative adult South African men (aged 18-35 years) undergoing voluntary medical male circumcision (vMMC). Migratory and non-migratory foreskin cells were isolated from the inner and outer foreskin using spontaneous migration and enzymatic digestion of remnant epidermal tissue respectively, and subsequently immunophenotyped using multiparameter flow cytometry (n=31). The optimal HIV infection model was determined through assessment of different infection models inclusive of i) epidermal sheets, ii) foreskin explants and iii) pluricellular suspension cells (n=5). Using the ex vivo pluricellular foreskin infection model of suspension cells (n=17), Subtype C transmitted founder (T/F) and chronic infection derived (CC) infectious molecular clones (IMCs) were used alongside Subtype B NL4-3 IMCs with CCR5, CXCR4 and BaL envelopes. The extent of HIV infection was quantified by measurement of p24 in different immune cell subsets over a time-course. The different HIV infected cell subsets were characterized using CD45, CD207, CD1a, CD11c, CD14, CD3, HLA-DR, CD80/86, CD209, CD206, CD169, CD4 and CCR5. Results: Foreskin myeloid cells contained a rare population of LCs (1.11 % ± 1.02 %;) that was predominantly migratory (p = 0.0084) and “macrophage-like” cells (9.87 % ± 9.64 %) that, in addition to being 8-fold more abundant (p